Short-Term Prognosis of Transient Ischemic Attack and Predictive Value of the ABCD2 Score in Hong Kong Chinese - Lai Hong Simon Chiu; Wah Hon Yau; Ling Pong Leung; Peter Pang; Chee Tat Tsui; Kuang An Wan; Thomas Tak-shun Au; Wing Chi Fong; Shun Hang Joseph Chung (Cerebrovascular Diseases Extra, 2014)
Background: Literature on prognosis of transient ischemic attack (TIA) in Chinese is scarce. The short-term prognosis of TIA and the predictive value of the ABCD2 score in Hong Kong Chinese patients attending the emergency department (ED) were studied to provide reference for TIA patient management in our ED. Methods: A cohort of TIA patients admitted through the ED to 13 acute public hospitals in 2006 was recruited through the centralized electronic database by the Hong Kong Hospital Authority (HA). All inpatients were e-coded by the HA according to the International Classification of Diseases, Ninth Revision (ICD9). Electronic records and hard copies were studied up to 90 days after a TIA. The stroke risk of a separate TIA cohort diagnosed by the ED was compared. Results: In the 1,000 recruited patients, the stroke risk after a TIA at days 2, 7, 30, and 90 was 0.2, 1.4, 2.9, and 4.4%, respectively. Antiplatelet agents were prescribed in 89%, warfarin in 6.9%, statin in 28.6%, antihypertensives in 39.3%, and antidiabetics in 11.9% of patients after hospitalization. Before the index TIA, the prescribed medications were 27.6, 3.7, 11.3, 27.1, and 9.7%, respectively. The accuracy of the ABCD2 score in predicting stroke risk was 0.607 at 7 days, 0.607 at 30 days, and 0.574 at 90 days. At 30 days, the p for trend across ABCD2 score levels was 0.038 (OR for every score point = 1.36, p = 0.040). Diabetes mellitus, previous stroke and carotid bruit were associated with stroke within 90 days (p = 0.038, 0.045, 0.030, respectively). A total of 45.4% of CTs of the brain showed lacunar infarcts or small vessel disease. There was an increased stroke risk at 90 days in patients with old or new infarcts on CT or MRI. Patients with carotid stenosis ≥70% had an increased stroke risk within 30 (OR = 6.335, p = 0.013) and 90 days (OR = 3.623, p = 0.050). Stroke risks at days 2, 7, 30, and 90 in the 289 TIA patients diagnosed by the ED were 0.35, 2.4, 5.2, and 6.2%, respectively. Conclusion: The short-term stroke risk in Hong Kong Chinese TIA patients is low. The administered nonurgent treatment cannot solely explain the favorable outcome, the lower risk can be due to the different pathophysiological mechanisms of stroke between Caucasians and Chinese. The predictive value of the ABCD2 score is low in our population.